Study on shear creep model of calcareous sand in China South Sea - Bin Tang; Bin Tang; Xingyun Huang; Weitao Zhong (Frontiers in Earth Science)
The creep characteristics of calcareous sand have an important impact on the stability of the structures on the coral islands in the South China Sea. Among the existing creep models for calcareous sand, fewer models consider the particle fragmentation of calcareous sand, which cannot accurately describe the shear creep of calcareous sand around the foundation of island structures. To study the shear creep model of calcareous sand, direct shear creep tests under different vertical and shear stresses and particle sieving tests of calcareous sand before and after the creep tests were carried out on calcareous sand. The results showed that the shear creep curve of calcareous sand exhibits nonlinearity with time, and can be divided into decelerated creep stage and stable creep stage; calcareous sand has different degrees of particle fragmentation during the shear creep test, and the degree of particle fragmentation is greater with the increase of the shear stress level. Based on the test results, combined with the Singh-Mitchell model theory, a model parameter on particle crushing was introduced, and a shear creep model considering particle crushing was established. Through validation, the model curve is closer to the experimental curve and can accurately describe the shear creep of calcareous sand in the South China Sea reefs.